G183(P) A novel way to score the autism spectrum quotient questionnaires and childhood autism spectrum tests. (12th March 2018) - Patel, LB; Stuart-Booth, S; Rakshi, K
Abstract : Aims: The incidence of autism in the UK is predicted at 0.1%; 1 00 000 children and 7 00 000 adults. Diagnosis of Autism Spectrum Disorder (ASD) varies regionally though national standards are outlined; NICE Clinical guideline (CG128) and Quality standard (QS51). The use of questionnaires to assess for Autism Spectrum Disorder (ASD) in community child health services, is common practice. Questionnaires are sent to both parents and caregivers and the school. Returned questionnaires are then hand scored by clinicians. Questionnaire scores alongside history, clinical examination and multidisciplinary assessment are used to inform diagnoses. The Autism Spectrum Quotient: Children's Version (AQ-Child) and Adolescent's Version (AQ-Adol) and Childhood Asperger Syndrome Test (CAST) have been widely used in the NHS for 10 and 15 years, respectively. The AQ includes 50, 4 point Likert scale questions and the CAST includes 39 binary yes/no questions. Scoring questionnaires can take several minutes each and is usually done by comparing answers to an A4 paper score sheet. In order to improve cost effectiveness and ultimately service delivery we explored ways to score questionnaires more efficiency. Methods: Relevant published literature on the method of scoring AQ-Child, AQ-Adol and CAST questionnaires was sought from Ovid MEDLINE 1946–2017. Search criteria included; English language and studies specifically detailing the scoring of the AQ-Child, AQ-Adol and CAST. Unpublished data on local practice was also sought from international search engines; Google, Bing and Yahoo. We devised specifically sized acetates which are made to be placed over the completed AQ-Child, AQ-Adol and CAST questionnaires to enable scoring. Results: No published or unpublished data was found to evidence any methods of scoring the AQ-Child, AQ-Adol and CAST questionnaires away from the conventional score sheets. Our locally designed and produced acetates when placed above the AQ-Child, AQ-Adol and CAST questionnaires significantly reduced scoring time. Conclusion: Our designs for scoring the AQ-Child, AQ-Adol and CAST questionnaires are entirely novel and unique. Locally, they have significantly increased efficiency and cost effectiveness. As pressures on our services continue to increase this is a welcome step in improving service delivery and patient care.